Bee (Hymenoptera: Apoidea) and hoverfly (Diptera: Syrphidae) pollinators in Pannonian habitats of Serbia, with a description of a new Eumerus Meigen species (Syrphidae) - Markov, Zlata; Nedeljković, Zorica; Ricarte, Antonio; Vujić, Ante; Jovičić, Snežana; Józan, Zsolt; Mudri-Stojnić, Sonja; Radenković, Snežana; Ćetković, Aleksandar (Zootaxa, 2016)
The diversity of bee (Hymenoptera: Apoidea) and hoverfly (Diptera: Syrphidae) pollinators from ten localities in Vojvodina, Serbia was surveyed. Among different types of Pannonian habitat (grasslands, heathland and scrub, woodland and forest habitats) all localities were categorised as forest and steppe. They were in protected areas, mostly undisturbed by human activity. Censuses of pollinators took place from 30 March to 10 October, 2014. We recorded 218 pollinator species; 135 bee species (42 Halictidae; 32 Apidae; 29 Andrenidae; 24 Megachilidae; 7 Colletidae; 1 Melittidae) and 83 species of hoverflies. We describe a new species of hoverfly, Eumerus pannonicus sp. nov., and compare it to other similar species. Based on our study, the Special Nature Reserve of Pašnjaci Velike Droplje is critical for the conservation of this new Eumerus—being only found at this locality—and other species such as Chrysotoxum lineare (Zetterstedt), which is rare in Europe and protected under Serbian legislation. The highest numbers of bee species were recorded in the Deliblato and Subotica sand areas (40 and 32, respectively), while Fruška Gora Mountain and the Vršac Mountains harboured the highest number of hoverfly species.